Nuer Religion - Evans-Pritchard, Edward E. (Oxford University Press, 1956)
A study of Nuer religion is a study of what they consider to be the nature of Spirit and of man's relation to it. I had previously spent many months among the Azande people of the Nile-Uelle divide. From my earliest days among them I was constantly hearing the word mangu, witchcraft, and it was soon clear that if I could gain a full understanding of the meaning of this word I should have the key to Zande philosophy. When I started my study of the Nuer I had a similar experience. I constantly heard them speaking of kwoth, Spirit, and I realized that a full understanding of that word was the key to their – very different – philosophy. The attempt to reach it and, even more, to present my conclusions has occupied me for a long time and has proved to be a formidable task. The difficulties which had to be overcome will be very apparent in the pages which follow, but I mention some of them now. – from Preface (p. vi.).
free
Keywords: History / Europe / Eastern